2015
DOI: 10.1155/2015/684708
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Practice and Perspectives of Chinese Acupuncturists onDeqi

Abstract: Deqi refers to the special sensation and reaction sensed mainly by both acupuncturist and patient when a needle was inserted into the acupoints and is considered to be vital to achieve acupuncture effect. For acupuncturist, it is important to judge and control Deqi in clinical practice. However, enough attention is paid to patients' feelings rather than acupuncturists' nowadays. We thus conducted this survey to determine acupuncturists' perspectives about Deqi and to further find the proper way to induce Deqi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This is based on the fact that this sensation has been clinically related to the effectiveness of the acupuncture. 36,37 In addition, the use of the GV20 and BL60 acupuncture points may have influenced the improvements obtained in dynamic balance. We consider that this may be due to the toning and strengthening effect of the energy's body and the spine and lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the fact that this sensation has been clinically related to the effectiveness of the acupuncture. 36,37 In addition, the use of the GV20 and BL60 acupuncture points may have influenced the improvements obtained in dynamic balance. We consider that this may be due to the toning and strengthening effect of the energy's body and the spine and lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…That means the needle must be inserted into the right depth (about 2 cm in lower limbs) and position ( π / ω cm around the acupoint in our simulation) to induce enough strain and stress. A survey showed that acupuncturists think deep insertion was easier to induce acupuncture sensations than shallow insertion [21].…”
Section: Discussionmentioning
confidence: 99%
“…The acupuncture needles will be inserted straightly or obliquely at a depth of 10–30 mm to effectuate the desired sensation of “De qi” (Table 2 ) by reinforcing-reducing techniques of lifting, thrusting, twisting, and rotating the needles moderately. When the acupuncture doctor feels sinking, astringent, and tightness around the needle by his/her finger while the patient senses soreness, numbness, distension, and heaviness around the acu-point, this will be considered the arrival of the “De qi” sensation [ 22 ]. All the needles will be retained for 20 min.…”
Section: Methodsmentioning
confidence: 99%